Alfred Marshall's Mission. - Reisman, David A. (Routledge revivals., 2013)
Alfred Marshall was anxious to do good. Intended by an Evangelical father for the vocation of clergyman, the author of the mould-shaping Principles of Economics remained to the end of his days a great preacher deeply committed to raising the tone of life. First published in 1990, Alfred Marshall's Mission explains how this most moral of political economists sought to blend the downward sloping utility function of Jevons and Menger with the organic evolutionism of Darwin and Spencer, how this celebrated theorist of social alongside economic growth sought to combine the math.